2019
DOI: 10.26499/ijea.v2i2.34
|View full text |Cite
|
Sign up to set email alerts
|

When National Examination No Longer Determining Graduation, Will Students Accomplish It Seriously?

Abstract: The National Examination in Indonesia, which began in 2015, was no longer a determinant of student graduation at the end of the education level. Utilization of the examination results will affect the seriousness of the students in working on it. This study aims to describe the level of seriousness of 12th grade students in working on National   Examinations, when it no longer a determinant of graduation by examining teachers and school principals’ point of view. This research is a qualitative study by using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
2

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 7 publications
(11 reference statements)
0
4
0
2
Order By: Relevance
“…Third, the UN is no longer used as a determinant indicator of students' graduation, impacting a decrease in students' motivation and spirit to face the UN. The study by Retnawati et al (2019) reported that when the UN was not a graduation requirement in 2015, based on information from teachers and school principals, it could be concluded that students' preparation for the UN was greatly decreased. Students preferred to focus on preparing for college entrance exams.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the UN is no longer used as a determinant indicator of students' graduation, impacting a decrease in students' motivation and spirit to face the UN. The study by Retnawati et al (2019) reported that when the UN was not a graduation requirement in 2015, based on information from teachers and school principals, it could be concluded that students' preparation for the UN was greatly decreased. Students preferred to focus on preparing for college entrance exams.…”
Section: Discussionmentioning
confidence: 99%
“…The research findings indicate that students who are enthusiastic about achieving learning goals foster high motivation to learn to achieve learning goals. This motivation helps students improve learning outcomes (Retnawati et al, 2019). Learning motivation can influence and have a relationship with student learning outcomes (Sulistiyarini & Sukardi, 2016).…”
Section: Math Learning Outcomes With Aflmentioning
confidence: 99%
“…Most recently, the National Education Standards Agency of the Republic of Indonesia, as the authorized party in the implementation of the National Examination (NE), canceled the last NE in 2020 for secondary schools, which was an effort against the spread of the Covid-19 outbreak. This NE is planned to be the last since the policy was changed by NE with Asesmen Kompetensi Minimum (AKM) and character surveys (Retnawati et al, 2019).…”
Section: Introductionmentioning
confidence: 99%